Integrated metabolomics and lipidomics evaluate the alterations of flavor precursors in chicken breast muscle with white striping symptom - Kong, Fuli; Bai, Lu; He, Zhengxiao; Sun, Jiahong; Tan, Xiaodong; Zhao, Di; Feng, Furong; Liu, Dawei; Zhao, Guiping; Wen, Jie; Liu, Ranran (Frontiers in Physiology, 2023)
White striping (WS) is the most common myopathy in the broiler chicken industry. To reveal the flavor changes of WS meat objectively, the flavor precursors of WS breast muscle were evaluated systematically with integrated metabolomics and lipidomics. The results showed that WS could be distinguished from normal controls by E-nose and four volatile compounds were detected as decreased compounds by gas chromatography-mass spectrometry. Lipidomic analysis showed that WS breast fillets featured increased neutral lipid (83.8%) and decreased phospholipid molecules (33.2%). Targeted metabolomic analysis indicated that 16 hydrophilic metabolites were altered. Thereinto, some water-soluble flavor precursors, such as adenosine monophosphate, GDP-fucose and L-arginine increased significantly, but fructose 1,6-bisphosphate and L-histidine significantly decreased in the WS group. These results provided a systematic evaluation of the flavor precursors profile in the WS meat of broiler chickens.